Evaluation of Sweet Potato Leaves and Cassava Leaves Inclusions into the Diet Containing Lemuru Oil on Lipid Metabolism in Local Duck - U. Nurrofingah; Sumiati Sumiati; Y. Retnani (Tropical Animal Science Journal, 2020)
The objective of this study was to evaluate the effects of sweet-potato leaves and cassava leaves inclusions into the diet containing lemuru oil on lipid metabolism of local laying ducks. One hundred and eighty laying ducks with an average body weight of 1657 g were divided into 6 groups of experimental diets with 3 replications and 10 ducks in each replication. The experiment was arranged in a 2 x 3 factorial design. The first factor was the level of sweet potato leaves consisted of 2 levels, i.e., 0% and 5%. The second factor was the level of cassava leaves consisted of 3 levels, i.e., 0%, 5%, and 10%. The variables observed were performance of laying duck, blood, meat, and egg lipid profile, as well as the relationship between the average consumption of β-carotene with cholesterol concentration in the blood, egg, and meat of laying duck. The results showed that there was no interaction and no effect between sweet potato leaf meal (SPLM) and cassava leaf meal (CLM) on feed consumption. Different levels of SPLM and CLM gave a significant interaction effect (p<0.05) on body weight gain, with the best interaction, was 5% SPLM combined with 0% CLM (26.60 g/duck). There was also a significant interaction effect between the combination of 5% SPLM and 10% CLM (p<0.05) for reducing the cholesterol, triglyceride, and LDL concentrations in the blood, meat, and egg. Different levels of SPLM and CLM gave significant interaction effects (p<0.05) on the fat contents of flash in laying duck. The fat content of the liver was significantly decreased by 5% treatment of SPLM (p<0.05). Meat fat decreased significantly with a combination of 5% SPLM and 10% CLM (p<0.05). Treatments with 5% SPLM or 10% CLM reduced blood MDA (p<0.05), while treatments with 10% CLM reduced the MDA in the liver (p<0.05). It can be concluded that the combination of 5% SPLM and 10% CLM in the diets was effective as a source of antioxidants to protect unsaturated fatty acids in the blood, meat, and egg of ducks based on the reduced concentrations of cholesterol, triglyceride, and LDL.